Drivers of Customer Satisfaction in Malaysia’s Online Food Delivery Services: A Pilot Study - Mat Hasan, Nor Hasliza; Ibrahim, Nor Fauziana; Cha Jun, Koh (International Review of Management and Marketing, 2025)
This pilot study investigates factors influencing customer satisfaction in Malaysia’s online food delivery services. Using a quantitative approach, data were collected from 150 customers through an online survey. Structural Equation Modeling (SEM) was employed to analyse the relationships between system complexity, food quality, payment methods, service quality, time-saving, and customer satisfaction. Results indicate that system complexity, food quality, and service quality significantly impact customer satisfaction, while payment methods and time-saving do not. Food quality emerged as the strongest predictor of satisfaction. This study provides initial insights into customer preferences in Malaysia’s online food delivery market, offering a foundation for future comprehensive research and practical strategies for service providers.